Coreolanceolins A–E, New Flavanones from the Flowers of Coreopsis lanceolate, and Their Antioxidant and Anti-Inflammatory Effects - Kim, Hyoung-Geun (Antioxidants (Basel), 2020)
(1) Background: Many flavonoids derived from natural sources have been reported to exhibit antioxidant and anti-inflammatory effects. Our preliminary study suggested that Coreopsis lanceolata flowers (CLFs) include high flavonoid content; (2) Methods: CLFs were extracted in 80% (v/v) aqueous methanol and fractionated into ethyl acetate, n-butanol, and water fractions. Repeated column chromatographies for the organic fractions led to the isolation of seven flavanones. Quantitative analysis of the flavanones was carried out using reversed-phase high-performance liquid chromatography. All flavanones were evaluated for their antioxidant and pro-inflammatory inhibition effects; (3) Results: Spectroscopic analyses revealed the chemical structure of five new flavanones, coreolanceolins A–E, and two known ones. The content of the seven flavanones in extracts were determined from 0.8 ± 0.1 to 38.8 ± 0.3 mg/g. All flavanones showed radical scavenging activities (respectively 104.3 ± 1.9 to 20.5 ± 0.3 mg vitamin C equivalents (VCE)/100 mg and 1278.6 ± 26.8 to 325.6 ± 0.2 mg VCE/100 mg) in the DPPH and 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assays and recovery activities in Caco-2 (59.7 to 41.1%), RAW264.7 (87.8 to 56.0%), and PC-12 (100.5 to 69.9%) cells against reactive oxygen species. Furthermore, all flavanones suppressed nitric oxide production (99.5% to 37.3%) and reduced iNOS and COX-2 expression in lipopolysaccharide-treated RAW 264.7 cells; (4) Conclusions: Five new and two known flavanones were isolated from CLF, and most of them showed high antioxidant and pro-inflammatory inhibition effects.